Sharing rule identification for general collective consumption models - Laurens Cherchye; Bram De Rock; Arthur Lewbel; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2012)
We propose a method to identify bounds (i.e. set identification) on the sharing rule for a general collective household consumption model. Unlike the effects of distribution factors, it is well known that the level of the sharing rule cannot be uniquely identified without strong assumptions on preferences across households of different compositions. Our new results show that, though not point identified without these assumptions, bounds on the sharing rule can still be obtained. We get these bounds by applying revealed preference restrictions implied by the collective model to the household's continuous aggregate demand functions. We obtain informative bounds even if nothing is known about whether each good is public, private, or assignable within the household, though having such information tightens the bounds. An empirical application demonstrates the practical usefulness of our method.
urn:nbn:de:101:1-201301213655
Keywords: D11; D12; D13; C14; C30; 330; collective model; consumer demand; revealed preferences; sharing rule; identification; bounds; Mikroökonomische Konsumfunktion; Haushaltsökonomik; Offenbarte Präferenzen; Modellierung; Theorie